Asymmetric syntheses of (-)-1-deoxymannojirimycin and (+)-1-deoxyallonojirimycin via a ring-expansion approach. - Davies, S; Figuccia, A; Fletcher, A; Roberts, P; Thomson, J (2013)
The asymmetric syntheses of (-)-1-deoxymannojirimycin and (+)-1-deoxyallonojirimycin are described herein. The ring-closing iodoamination of two epimeric bishomoallylic amines to give the corresponding 5-iodomethylpyrrolidines was followed by in situ ring-expansion to give two diastereoisomerically pure (>99:1 dr) cyclic carbonates. Subsequent deprotection gave (-)-1-deoxymannojirimycin and (+)-1-deoxyallonojirimycin as single diastereoisomers in 7.4 and 3.3% overall yield, respectively, from commercially available starting materials.